Melanogenesis Inhibitory Effects of Ethanol Extract of Perilla frutescens’s Leaves on B16 Melanoma Cells: Perilla frutescens’s Leaves Melanogenesis Inhibitory Effects - Van Tran, Thuan; Nguyen-Ho, Quynh-Nhu; Nguyen-Thien, Truong-Van; Ton-That, Quang; Linh Tran, Thuoc; Tran-Van, Hieu (Iranian Journal of Pharmaceutical Sciences, 2021)
Perilla frutescens (L.) Britt. is a Vietnamese herb containing many polyphenol compounds potential on antioxidants and tyrosinase inhibitors for cosmetic applications. Natural compounds and products have got more attention as they have less undesirable side effects and satisfy the diverse needs of consumers that include anti-melanogenesis, antioxidation, etc. This study evaluated the antioxidant capacity, inhibition of melanin synthesis in B16 melanoma cells of perilla leaves ethanol extract (PEE). PEE showed the high antioxidant properties in vitro by 2, 2′-diphenyl-1-picrylhydrazyl radical assay (DPPH) and Ferric reducing antioxidant power (FRAP). In addition, PEE has inhibitory activities for mushroom tyrosinase (TYR). The results showed that concentrations of 100 - 300 μg/mL of PEE were not affected on B16 cell viability. In B16 cells, melanin content and cellular tyrosinase activity were significantly decreased in PEE-treated cells in a dose-dependent manner. These results suggested that Perilla frutescens (L.) Britt. had a great potential as natural sources which could be used as agents in skincare products.